Ficus Bengalensis Linn.- An Overview - VIKAS V. PATIL; VIJAY R. PATIL (International Journal of Pharma and Bio Sciences, 2010)
Since ancient times, plants have been an exemplary source of medicine. Ayurveda and other Indian literature mention the use of plants in treatment of various human ailments. Ficus bengalensis Linn is a large evergreen tree found throughout forest tracts of India. It is popular indigenous system of medicine like Ayurveda, Siddha, Unani and Homeopathy. In traditional system of medicine various plant parts such as stem bark, root bark aerial roots, vegetative buds, leaves, fruits and latex are used in dysentery, diarrhea, diabetes leucorrhoea, menorrhagia, nervous disorders, tonic and astringent. According to Ayurvedic system of medicine Ficus bengalensis Linn (Banyan tree) is well known to be useful in diabetes. The present review is therefore, an effort to give a detailed survey of the literature on its Pharamacognosy, phytochemistry, traditional and pharmacological uses.